2018
DOI: 10.1111/papr.12729
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Postoperative Pain from Assessment of Pain Associated With Venous Cannulation

Abstract: Background It has previously been reported that venous cannulation‐induced pain (VCP) can be used to predict acute postoperative pain after laparoscopic cholecystectomy. Patients rating VCP at ≥2.0 VAS units had 3.4 times higher risk for moderate or severe pain. The purpose of this study was to evaluate if VCP scores of ≥2.0 VAS units are associated with higher risk for acute postoperative pain after various common surgical procedures. Methods In a prospective clinical observational study, 600 male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Furthermore, the cut-off level of the VCP was found to be 2.0 VAS units in predicting postoperative pain in Persson et al Study [9]. Another study reported that 2.0 VAS units represented a more reasonable cut-off level of VCP for prediction of postoperative pain [12].…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the cut-off level of the VCP was found to be 2.0 VAS units in predicting postoperative pain in Persson et al Study [9]. Another study reported that 2.0 VAS units represented a more reasonable cut-off level of VCP for prediction of postoperative pain [12].…”
Section: Discussionmentioning
confidence: 86%
“…Carvalho et al [13] study used VCP score to predict pain during childbirth in a cohort of 50 women admitted for induction of labour and found that intense pain upon intravenous cannulation predicted an earlier request for epidural analgesia during the course of induction of labour. A recently study [12] evaluated the usefulness of VCP score in 4 categories surgery (presumed to with hardly any postoperative pain, slight, moderate and severe levels of postoperative pain) and reported that the method of VCP score was only statistically significant in the patients subjected to surgery presumed to result in moderate levels of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore included patients subjected to different kinds of surgery and anesthesia, well aware that this would give us a highly heterogeneous cohort and enable us to show if this test is also useful in broader perioperative clinical perspectives. 1 We adjusted for intraoperative use of regional anesthesia to take into account the potential influence on immediate postoperative pain levels, as shown in table 5, and found no predictive ability of the VCP test in patients with regional anesthesia, most likely because of their lower levels of acute postoperative pain.Their second concern is on lack of standardization of the postoperative analgesic regimen, which might have had a direct confounding effect on the primary outcome. Certainly, the treatment of postoperative pain was nonstandardized but instead adhered to current clinical practice and standards of care.…”
mentioning
confidence: 99%
“…We therefore included patients subjected to different kinds of surgery and anesthesia, well aware that this would give us a highly heterogeneous cohort and enable us to show if this test is also useful in broader perioperative clinical perspectives. 1 We adjusted for intraoperative use of regional anesthesia to take into account the potential influence on immediate postoperative pain levels, as shown in table 5, and found no predictive ability of the VCP test in patients with regional anesthesia, most likely because of their lower levels of acute postoperative pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation